2015
DOI: 10.4236/ijmpcero.2015.44034
|View full text |Cite
|
Sign up to set email alerts
|

Beam Characteristics at Low Dose Monitor Unit Settings for Vero4DRT

Abstract: The stability of delivery of low monitor unit (MU) setting is important especially for step-andshoot intensity-modulated radiotherapy (IMRT), because the nature of the technique is inherent to repeat beam on/off according to the number of the segments. This study evaluates the dose linearity and profile flatness/symmetry under low MU settings for Vero4DRT, a new linear-accelerator based irradiation system that currently implements step-and-shoot IMRT. To evaluate the dose linearity and flatness/symmetry, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Reena et al .,[ 7 ] Bhangle et al .,[ 8 ] and Miura et al . [ 13 ] recommended ≥4 MU, <5 MU, and 5 MU, respectively. Our results showed that the treatment delivered with <3 MU settings can result in an error in dose delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reena et al .,[ 7 ] Bhangle et al .,[ 8 ] and Miura et al . [ 13 ] recommended ≥4 MU, <5 MU, and 5 MU, respectively. Our results showed that the treatment delivered with <3 MU settings can result in an error in dose delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have reported the characteristics of low MU such as stability, linearity, flatness, symmetry, and reproducibility for various linear accelerators from Elekta, Siemens, and Varian. [ 4 5 6 7 8 9 10 11 12 13 ] Different results were reported for the same make of the linear accelerator, which revealed that the characteristics of the beam differ between the machines.…”
Section: Introductionmentioning
confidence: 99%
“…of the MLC for MHI-TM2000 using a well-commissioned 6-MV photon beam, EDR2 films, and water-equivalent phantoms [5]. Miura et al reported the dose linearity and profile flatness/symmetry under low-MU settings of Vero4DRT under low-MU settings [10]. Because the Novalis system likewise supports only iPlan RT, dosimetric characteristics of the Novalis may serve as a reference [11].…”
Section: Measurementmentioning
confidence: 99%